Incorporación de radioestroncio por organismos marinos - Cancio, David; Llauró, J.A.; Ciallella, Norberto R.; Beninson, Dan Jacobo (International Atomic Energy Agency, 1973)
Fil: Cancio, David Comisión Nacional de Energía Atómica; Argentina